Character Likes to Read in Elementary School Students Electronic Module and Print Module - Asrial, Asrial; Syahrial, Syahrial; Kurniawan, Dwi Agus; Luthfiah, Qonita (Universitas Pendidikan Ganesha, 2021)
The low reading character is often found in the school environment. The low reading character is that many students read textbooks. This is due to the lack of exciting strategies to motivate students to read. This study aims to analyze the comparison of teaching materials, namely, comparing the print module and the electronic module. This type of research is comparative research. The method used in this study is a quantitative method using a survey research design. The sample of this study was the fourth-grade students who opened 22 people. Data analysis used descriptive, inferential statistics, namely analyzing data by describing the data that had been collected. The results of this study are from the two teaching materials that are applied, namely the printed module and the electronic module. It can see indicators of the reading habit. In the study, the dominant results were good for looking at indicators of reading fondness characters with the application of electronic modules. In contrast, for the application of print modules in the good category, from this it was seen that the difference between the two learning materials was applied to see indicators of reading fondness characters, this is with the results of the t-test which has been done, where the obtained is smaller than 0.05 then there is a difference between the two. So the electronic module based on local wisdom needs to be applied by teachers to instill the character of reading fondness among students.